Badania ankietowe pracodawców w aglomeracji wrocławskiej - analiza statystyczna tablic dwudzielczych - Kozyra, Cyprian; Marciniuk, Agnieszka (Survey research of employers - the analysis of statistical contingency tables, 2008)
The research of labour market in Wroclaw agglomeration, to which nine Lower Silesian povicits (Polish county) - Milicz, Oleśnica, Oława, Strzelin, Środa Śląska, Trzebnica, Wołow, Wroclaw rural poviat and Wroclaw city belong, was conducted in 2005. The research was based on data collected from a survey of employers. According to official statistics, there are 149 483 enterprises in Wroclaw agglomeration. The survey sample was formed by two thousand micro, small, middle, and big firms. The article covers only results for micro firms because population of these firms is the most numerous. The authors present the statistical analysis of contingency tables based on two chi-square tests: independence and goodness of fit tests. There are dependences in all analyzed questions. The results are as follows: the number of workers depends on planned changes and on educational status. The assessment of quality of education depends on educational status. The form of employment depends on educational status. It is foreseen a trend for future employment growth. The appreciation of workers qualifications and the economic situation of a firm influence the employment. The main way of getting a job is through personal contacts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 90-102